Studi eksperimental terhadap porositas dan hambat alir udara pada komposit penyerap suara - Sari, N.H.; Fajrin, J.; Yudhyadi, I.G.N.K. (Universitas Mataram, 2018)
In this paper, we present a comprehensive analytical and experimental investigation for the determination of the air flow resistivity and porosity of sound absorber composite. The ratio of the volume fraction of fiber and polyester resin is 15, 25, 35, 55 and 65 (%).The dimensions of the absorbent composite sample are 29 mm x 20 cm (diameter x thickness). Porosity and Air flow resistivity of composites have been investigated. The results showed that the porosity of the composites increased with increasing amount of fiber due to the interface between fiber and resinless dense. In contrast, the air flow resistivity values are lower with a denser resin and fiber interface.